IDENTIFICATION OF MALARIA INCIDENCE IN LANGKAT REGENCY NORTH SUMATERA PROVINCE - Rahmadani Sitepu; Irnawati Marsaulina; Nurmaini; Taufik Ashar (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Malaria was transmitted through the bite of female Anopheles mosquitoes which is still a threat to global health including Indonesia which is a tropical country. This study aimed to identify the number of malaria cases in Langkat Regency, North Sumatera province. This research used a descriptive approach using secondary data on malaria at the North Sumatra Provincial Health Office and the Langkat District Health Office. Secondary data was viewed and identified based on the annual report on malaria incidence from 2016 to 2021. There were 125 cases of malaria in Langkat Regency in 2016. In 2017 a total of 93 cases of malaria were recorded with the highest cases in Kuala District (41.9%) and the lowest in Bahorok District (3.2%). There were 51 confirmed cases of malaria in 2018, with Kuala District having the greatest number of cases (54.9%) and the lowest in Padang Tualang District (2%). In 2019, there were 10 malaria cases with the highest cases in Kuala District (40%) and the lowest in Kutambaru District (10%). There were 26 cases of malaria reported in 2020, with Kutambaru District having the greatest percentage of infections (84.6%), and in 2021 Kutambaru District had a highest cases of malaria (91.2%) from 34 total cases. There was a decrease in the incidence of malaria from 2016 to 2019, but it increased again in 2020 and 2021. Serious attention is needed from all related parties, such as the Langkat Regency government, the North Sumatra Provincial Hhealth Office, or the Langkat Regency health office.